2021
DOI: 10.1002/btpr.3136
|View full text |Cite
|
Sign up to set email alerts
|

A rapid novel strategy for screening of antibody phage libraries for production, purification, and functional characterization of amber stop codons containing single‐chain antibody fragments

Abstract: Phage display antibody (PDA) libraries, allows the rapid isolation and characterization of high specificity monoclonal antibodies for therapeutic and diagnostic applications.However, selection of positive binding clones from synthetic and semi-synthetic libraries has an inherent bias towards clones containing randomly generated amber stop codons, complicating the identification of high affinity binding antibodies. We screened Tomlinson I and J library against receptor binding domain (RBD) of SARS CoV2, eight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Tomlinson I + J libraries are widely used, based on scFv format with diversity of 18 amino acids incorporated in CDRs 2 and 3 in positions involved in antigen binding, and are highly diverse in the natural repertoire. Many studies used this library, and their antibody showed high specificity and binding affinity to the targets. …”
Section: Discussionmentioning
confidence: 99%
“…Tomlinson I + J libraries are widely used, based on scFv format with diversity of 18 amino acids incorporated in CDRs 2 and 3 in positions involved in antigen binding, and are highly diverse in the natural repertoire. Many studies used this library, and their antibody showed high specificity and binding affinity to the targets. …”
Section: Discussionmentioning
confidence: 99%
“…The cells were transiently transfected with the expressing plasmids. The supernatant was collected after 5–6 days, and the soluble protein was purified using Ni-NTA affinity chromatography with Ni 2+ ions immobilised on a resin by covalent attachment to nitrilotriacetic acid (NTA) (QIAGEN, Germany), as described (Parray et al 2020 ; Perween et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant proteins were expressed using the Expi 293 F expression system, from a codon-optimized nucleic sequence of RBD-His, Spike-His, HA-His, following the methodology published earlier [14] , [15] , [16] . Briefly, the culture supernatant was harvested 5-7 days post-transfection and purified by Ni-NTA affinity chromatography followed by dialysis in phosphate buffer saline (pH 7.4) as described in our previous papers [14] , [15] , [16] , [17] . The N protein of SARS-CoV-2 was expressed in the bacterial expression system and was purified by Ni-NTA affinity chromatography.…”
Section: Methodsmentioning
confidence: 99%